Analysis of Supply Chain in Investment Activity in the Russian Agricultural Complex - Valerievna Vaganova, Oksana; Evgenyevna Solovjeva, Natalya; Nikolaevich Polukhin, Oleg; Mikhailovich Zakharov, Victor; Gennadevna Zabnina, Galina; Lesovik, Ruslan Valerievich; Lesovaya, Svetlana Leonidovna; Evgenevna Ageykina, Mariya (International Journal of Supply Chain Management, 2020)
Abstract- The article analyzes supply chain in investment attractiveness and capital supply chain in investments in the Russian agro-industrial complex. The authors analyze the current state of the Russian agro-industrial complex, study supply chain in investments in fixed assets in the agricultural sector, and identify the growth rates of the components of GDP production. A supply chain forecast is carried out until 2024, and the share of supply chain strategies of agriculture markets in fixed assets to gross domestic product is also forecasted. In addition, the article reviews the structure of the components of gross domestic product in order to identify supply chain strategic directions for ensuring the country's food security.